Accessory cavitated uterine mass in a young female with chronic pelvic pain and dysmenorrhea - Deepti Naik (Asian Journal of Medical Sciences, 2024)
Accessory and cavitated uterine mass is a rare form of developmental Mullerian anomaly seen in young females, which presents as chronic recurrent pelvic pain and severe dysmenorrhea. Hysterosalpingography (HSG), ultrasonography, and magnetic resonance imaging (MRI) are the mainstay of diagnostic imaging. This entity is often underdiagnosed; therefore, a high index of suspicion combined with HSG and MRI imaging can help in making an accurate and timely diagnosis and thus prevent unnecessary interventions.